2023
DOI: 10.3390/brainsci13081186
|View full text |Cite
|
Sign up to set email alerts
|

Telestroke: A Novel Approach for Post-Stroke Rehabilitation

Abstract: Despite the tremendous technologic advancements of recent years, the prevalence of stroke has increased significantly worldwide from 1990 to 2019 (a 70 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…TR offers a potential solution to some of the accessibility challenges faced by individuals living with stroke [2,4]. A study found that TR interventions for stroke found no change between telehealth and face-to-face interventions for activities of daily living, balance, and upper extremity involvement [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TR offers a potential solution to some of the accessibility challenges faced by individuals living with stroke [2,4]. A study found that TR interventions for stroke found no change between telehealth and face-to-face interventions for activities of daily living, balance, and upper extremity involvement [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Diana et al in 2017 emphasized the importance of clear outcome measurements with a focus on TR and VR [10]. However, there remains a lack of consensus regarding the utilization of outcome measures to enable meaningful appraisals across interventions and studies [4]. This gap in consensus has persisted from January 2015 until the present day, especially within the realm of TR.…”
Section: Introductionmentioning
confidence: 99%